CASE STUDIES OF PRIVATE GOVERNMENT COOPERATION: PROCUREMENT OF LAND DEVELOPMENT PROJECTS TOLL ROAD KRIAN – LEGUNDI – BUNDER – MANYAR - Prasetyo Adi Sungkono; H Fredy Kurniawan (NAROTAMA UNIVERSITY, Indonesia)
One of the efforts to maintain and enhance the economic growth of a region is supported by the existence of infrastructure development. Infrastructure development in the form of a toll road could increase the potential for the development of the economy of the region through improved the smooth flow of goods and services. Toll road construction project Krian– Legundi – Bunder – Manyar areas is one of national strategic Project (PSN) that are in the shadow of the State Ministry of Public Works and Public Housing (PUPR) with PT. Waskita Bumi Wira as the initiator. The research method used is descriptive qualitative, i.e. by doing observation and interviews with related parties on the project construction of KLBM toll road. The results of this study are: (i) the forms of cooperation carried out in the construction of KLBM toll roads, is Build Operate Transfer (BOT); (ii) the process of acquiring the land in KLBM toll road development projects are the responsibility of PT WBW assisted by PPK Land Procurement and BPN Sidoarjo and Gresik Regency; (iii) Proceedings reversion bailouts land is done through examination by the BPKP and then verified by the LMAN and the value of payments carried out as stated in the agreement.